Adjuvant effect of Bacillus firmus in intranasal immunization of guinea pigs with inactivated type B infuenza virus - Havlícková, M; Prokesová, L; Zanvit, P; Tácner, J; Limberková, R (Folia microbiologica, 2006)
Intranasal immunization of guinea pigs with inactivated type B influenza virus plus inactivated Bacillus firmus as an adjuvant compared to the virus alone yields higher titers of serum hemagglutination-inhibiting antibodies and virus-neutralizing antibodies. This phenomenon could be useful in standard serology, especially in the preparation of immune sera against highly pathogenic strains for in vitro diagnosis.
Keywords: morčata; Vaccination; vakcíny proti chřipce; vakcinace; Adjuvants, Immunologic; Antibodies, Viral; Influenza Vaccines; Serologic Tests; Animals; protilátky virové; Bacillus; Influenza B virus; Guinea Pigs; sérologické testy; virus chřipky B; adjuvancia imunologická; zvířata